1993
DOI: 10.2307/1942094
|View full text |Cite
|
Sign up to set email alerts
|

Production in Natural and Restored Seagrasses: A Case Study of a Macrobenthic Polychaete

Abstract: Restoration of seagrass beds has been suggested as a method to correct declining vegetation cover in shallow waters. Secondary production of the polychaete Kinbergonuphis simoni was used to evaluate faunal equivalency of newly restored (2-yr-old) seagrass beds to beds that are mature (at least 17 yr old) in an embayment in Tampa Bay, Florida. Information on density of polychaetes, size structure, reproductive characteristics, and production (growth increment summation method) was collected from May 1989 to Feb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Our study indicated that, in the Galveston Bay system, nekton and benthos densities, numbers of taxa, and species composition in transplanted shoalgrass would take more than 3 years to reach equivalence with natural seagrass. Studies in Florida demonstrated that transplant beds reached densities and species compositions similar to those of reference sites in 1–2.3 years for nekton (Fonseca et al 1996) and in 2–4 years for annelids (Bell et al 1993). Benthic communities elsewhere also seem to reach equivalence faster than in Galveston Bay, for example, after 7 months in North Carolina (Homziak et al 1982) and after 9 months in Oregon (Posey 1988).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our study indicated that, in the Galveston Bay system, nekton and benthos densities, numbers of taxa, and species composition in transplanted shoalgrass would take more than 3 years to reach equivalence with natural seagrass. Studies in Florida demonstrated that transplant beds reached densities and species compositions similar to those of reference sites in 1–2.3 years for nekton (Fonseca et al 1996) and in 2–4 years for annelids (Bell et al 1993). Benthic communities elsewhere also seem to reach equivalence faster than in Galveston Bay, for example, after 7 months in North Carolina (Homziak et al 1982) and after 9 months in Oregon (Posey 1988).…”
Section: Discussionmentioning
confidence: 94%
“…Functional equivalence in processes such as nutrient cycling, primary and secondary productivity, predation, or growth rates has rarely been addressed, perhaps because it is more costly and time‐consuming to test. To our knowledge, Bell et al (1993) provided the only published comparison of secondary production rates in restored and natural seagrasses, and this was for only a single species of polychaete. The database necessary to predict structural equivalence of restored and natural seagrass systems remains small (only a few sites around the world), and if the literature we cite herein is any indication, variation in restoration response and success criteria is large.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At any given time the density of burrows present may range from less than a few hundred per m 2 made by such large animals as lobsters, crabs, and shrimp (e.g., Webb and Eyre, 2004), to as high as several thousand individuals per m 22 in sediments inhabited by such smaller animals as marine annelids (e.g., Bell et al, 1993) and arthropods (e.g., amphipods; Pearson and Gingras, 2006). Burrowing activities increase the area of the sediment-water interface by as much as ten-fold: the amount of area increase depends on the burrow architecture and the population density (Koretsky et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses conducted to date on functional performance other than primary production in restored seagrass sites, have focused on infauna (Bell et al 1993;Sheridan et al 2003;Sheridan 2004b) or epibenthic invertebrates (Fonseca et al 1990(Fonseca et al , 1996. These studies have been limited to restoration sites where seagrass has been transplanted.…”
Section: Increased Protection For Seagrasses By National Governments mentioning
confidence: 99%